The derived p-length of a p-solvable group with bounded indices of Fitting p-subgroups in its normal closures - Trofimuk, A. A.; Gritsuk , D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 512.542 Let G be a p-soluble group. Then G has a subnormal series whose factors are p^′-groups or abelian p-groups. The smallest number of abelian p-factors of all such subnormal series of G is called the derived p-length of G. A subgroup H of a group G is called Fitting if H≤ F (G) . A functional dependence of the estimate of the derived p-length of a p-soluble group on the value of the indexes of Fitting p-subgroups in its normal closures is established.